Analysis of the Influence of Human Capital and Organizational Citizenship Behavior on the Service Performance of Medical Personnel at Dr. Haulussy Ambon Public Hospital - Novalien Carolina Lewaherilla; Harvey Hiariej (Universitas Padjadjaran, 2023)
The matters related to human capital and organizational citizenship behavior related to service performance in hospitals are measly limited to be studied. Therefore, through the research, the possibility of the problems is explored. The purpose of this study was to analyze the effect of human capital and organizational citichenzip behavior on the service performance of medical staff at Dr. Haulussy Ambon General Hospital. The research design is an associative explanatory survey, which is a study that purposes to reveal the correlation and contribution between human capital variables and organizational citichenzip behavior on service performance. The object of this research is Dr. Haulussy Ambon Hospital with a sample of 66 medical staff that was used as research respondents. The results of the study show that human capital has a significant and positive effect on the service performance of medical personnel; organizational citichenzip behavior has a significant and positive effect on the service performance of medical personnel. The suggestions that can be submitted are prioritizing human capital in optimizing service performance by encouraging an increase in the knowledge, expertise, skills, and abilities of medical personnel related to the demands for service needs that must be realized at Dr. Haulussy Ambon Public Hospital.